Long-term economic growth projections in the Shared Socioeconomic Pathways. (January 2017) - Dellink, Rob; Chateau, Jean; Lanzi, Elisa; Magné, Bertrand
Highlights: A detailed macroeconomic framework that describes the evolution of different drivers of economic growth is introduced. Long-term GDP and (per capita) income projections are made for 184 countries. Economic projections for the five Shared Socioeconomic Pathways (SSPs) are presented. Abstract: Long-term economic scenarios (up to 2100) are needed as a basis to explore possible different futures for major environmental challenges, including climate change. Given the high level of uncertainty involved, such scenarios would need to span a wide range of possible growth trajectories. The recently developed storylines of the Shared Socioeconomic Pathways (SSPs) provide a basis for making such projections. This paper describes a consistent methodology to derive (per capita) GDP trend pathways on a country basis. The methodology is based on a convergence process and places emphasis on the key drivers of economic growth in the long run: population, total factor productivity, physical capital, employment and human capital, and energy and fossil fuel resources (specifically oil and gas). The paper uses this methodology to derive country-level economic growth projections for 184 countries. The paper also investigates the influence of short-term growth rate estimates on the long-term income levels in various countries. It does so by comparing long-term projections based on short-term forecasts from 2011 with the projections based on forecasts from 2013. This highlights the effects of the recent economic crisis and uncertainty in short term developments on longer term growth trends. The projections are subject to large uncertainties, particularly for the later decades, and disregard a wide range of country-specific drivers of economic growth that are outside the narrow economic framework, such as external shocks, governance barriers and feedbacks from environmental damage. Hence, they should be interpreted with sufficient care and not be treated as predictions.